Conductive Nb25O62 and Nb12O29 anode materials for use in high-performance lithium-ion storage. (10th March 2018) - Li, Renjie; Qin, Yi; Liu, Xin; Yang, Liang; Lin, Chunfu; Xia, Ran; Lin, Shiwei; Chen, Yongjun; Li, Jianbao
Abstract: Conductive M–Nb V –O compounds are high-capacity, fast-charging, safe and stable anode materials that have potential use in lithium-ion batteries. However, their studies are very limited. Here, we facilely fabricate Nb25 O62 ( i.e., Nb IV Nb V 24 O62 ) and Nb12 O29 ( i.e., Nb IV 2 Nb V 10 O29 ) from high-temperature reduction of Nb2 O5 in a mixed H2 /Ar atmosphere. Nb25 O62 shows a monoclinic shear ReO3 crystal structure with a C2 space group and a structural unit containing a 3 × 4 octahedron-block and 0.5 tetrahedron, while Nb12 O29 shows a similar structure with an A2/m space group and a 3 × 4 octahedron-block. Their resulting open crystal structures lead to their large Li + -ion diffusion coefficients. Due to the unpaired 4 d electrons in Nb 4+, their electronic conductivities are increased by three orders of magnitude in comparison with Nb2 O5 . First-principles calculations even demonstrate their conductor characteristics. Hence, Nb25 O62 /Nb12 O29 exhibits comprehensively good electrochemical performance, including a significant pseudocapacitive contribution (72.7/79.0% at 1.1 mV s −1 ), high specific capacity (289/287 mAh g −1 at 0.1 C), high working potential (∼1.69/∼1.72 V vs. Li/Li + ), superior rate capability (133/165 mAh g −1 at 10 C) and prominent cyclic stability (only 0.3/14.5% capacity loss over 1000 cycles at 10 C). These findings demonstrate that Nb25 O62 and Nb12 O29 are promising anode materials for future use in high-performance lithium-ion storage. Graphical abstract: Image 1 Highlights: Nb25 O62 and Nb12 O29 are facilely prepared by high-temperature reduction of Nb2 O5 . Nb25 O62 /Nb12 O29 exhibits an open and stable shear ReO3 -type crystal structure. Nb25 O62 /Nb12 O29 has a large electronic conductivity and Li + diffusion coefficient. Nb25 O62 /Nb12 O29 shows significant pseudocapacitive behavior during the reaction. Nb25 O62 /Nb12 O29 has a high capacity, safety, rate capability and cyclic stability.